An Assessment in SpondyloArthritis International Society (ASAS)-endorsed definition of clinically important worsening in axial spondyloarthritis based on ASDAS - (:unkn) unknown (BMJ PUBLISHING GROUP, 2018)
Introduction In a previous phase, 12 draft definitions for clinically important worsening in axial spondyloarthritis (axSpA) were selected, of which 3 were based on absolute changes in Ankylosing Spondylitis Disease Activity Score (ASDAS)-CRP (ASDAS). The objective here was to select the best cut-off for ASDAS for clinically important worsening in axSpA for use in clinical trials and observational studies. Methods An international longitudinal prospective study evaluating stable patients with axSpA was conducted. Data necessary to calculate ASDAS were collected at two consecutive visits (spaced 7 days to 6 months). Sensitivity and specificity of the three cut-offs for change in ASDAS were tested against the patient's subjective assessment of worsening as the external standard (ie, the patient reporting that he had worsened and felt a need for treatment intensification). Final selection was made by a consensus and voting procedure among Assessment of SpondyloArthritis International Society (ASAS) members. Results In total, 1169 patients with axSpA were analysed: 64.8% were male and had a mean age of 41.7 (SD 12.4) years. At the second visit, 127 (10.9%) patients judged their situation as worsened. Sensitivity and specificity for an increase of at least 0.6, 0.9 and 1.1 ASDAS points to detect patient-reported worsening were 0.55 (Se) and 0.91 (Sp), 0.38 (Se) and 0.96 (Sp), and 0.33 (Se) and 0.98 (Sp), respectively. The ASAS consensus was to define clinically important worsening as an increase in ASDAS of at least 0.9 points. Conclusion This data-driven ASAS consensus process resulted in an ASDAS-based cut-off value defining clinically important worsening in axSpA for use in trials.
Keywords: ACTIVITY SCORE ASDAS; ANKYLOSING-SPONDYLITIS; DESIR COHORT